On social networking in intermittently connected networks. (2015) - Altamimi, Ahmed B.; Gulliver, T. Aaron
An intermittently connected network (ICN) is defined as a mobile network that uses cooperation between nodes to facilitate communication. This cooperation consists of nodes carrying the messages of other nodes in order to deliver it to the destination. An ICN does not require an infrastructure and does not track message routing, which is an attractive networking environment. However, delivering messages with low overhead is challenging when there is no routing information or networking infrastructure. In this work, social networking is exploited to obtain a high delivery rate while maintaining a low overhead ratio. This is achieved by allowing all communities participate in message delivery. Previously, only the source and destination communities were considered for this task, whereas in this work all communities participate. Results are presented which show that having all communities involved in message delivery in an ICN can greatly improve the probability of message delivery.